2011
DOI: 10.1093/anatox/35.7.394
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in Postmortem Toxicology

Abstract: Cannabinoids are often excluded from postmortem toxicology screens due to their ubiquitous nature, interpretative difficulties and unanswered questions regarding their postmortem redistribution. In this study, we review 30 postmortem cases where a drug screen gave a positive cannabinoids result and a confirmation identified Δ⁹-tetrahydrocannabinol (THC), 11-hydroxy-Δ⁹-tetrahydrocannabinol (11-OH-THC), and/or 11-nor-9-carboxy-Δ⁹-tetrahydrocannabinol (THC-COOH) in peripheral (BL-P) or cardiac/central blood (BL-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…33 Our finding of association of respiratory depression with FAAH gene (especially AA genotype of rs324420) may have potential significance for millions of patients prescribed and individuals abusing opioid agonists and/or cannabinoids (e.g. marijuana, synthetic cannabinoids) 22 , 34 39 every year, for both the abuse potential and the potential for life-threatening respiratory depression.…”
Section: Discussionmentioning
confidence: 89%
“…33 Our finding of association of respiratory depression with FAAH gene (especially AA genotype of rs324420) may have potential significance for millions of patients prescribed and individuals abusing opioid agonists and/or cannabinoids (e.g. marijuana, synthetic cannabinoids) 22 , 34 39 every year, for both the abuse potential and the potential for life-threatening respiratory depression.…”
Section: Discussionmentioning
confidence: 89%
“… reported a mean age of 33 years (range 15–66 years) for their study investigating the frequency of THC in driving under the influence of drugs (DUID) cases in Sweden. Mean and median ages were 38.2 and 35 years, respectively, in a study of postmortem cannabinoid concentrations from 30 autopsy cases .…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the Office of the Chief Medical Examiner of San Francisco, California reported that, of 1338 postmortem toxicology cases from July 1, 2010 to June 30, 2011, cannabinoids were confirmed in 30 (2.2%) accidental deaths (27). The Florida Department of Law Enforcement reported a 4.3% positive rate in postmortem cases in 2012 (28). Positive rates for cannabinoids in automobile drivers in three recent roadside studies were 7.7% in Spain, 8.5% in California (USA), and 9.8% in Australia (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…People may survive for hours following a collision and there will be ongoing distribution and metabolism of THC during that time. In the Vancouver region, where many of our cases came from, 50% of trauma deaths occur more than 6 hours after injury . Beckson cites a postmortem study by Drummer et al .…”
mentioning
confidence: 88%